Redescription of the Hyoid Apparatus and Associated Musculature in the Extant Coelacanth Latimeria chalumnae: Functional Implications for Feeding. Issue 3 (8th January 2015) - Dutel, Hugo; Herrel, Anthony; Clément, Gaël; Herbin, Marc
ABSTRACT The coelacanth Latimeria is the only extant vertebrate in which the neurocranium is divided into an anterior and a posterior portion which articulate by means of an intracranial joint. This articulation is thought to allow an elevation of the snout up to 20‐degree angle, which is supposed to enhance mouth gape and velocity, in turn allowing for a powerful suction. Several functional models have been proposed to explain the skull movement in Latimeria, but they disagree on the mechanisms responsible for mandibular depression and intracranial elevation, and more precisely on the role and mobility of the hyoid apparatus during these processes. We here show that the m. coracomandibularis spans ventrally to the palate‐mandible joint, and is likely involved in mandibular depression. The hyoid apparatus is sheathed by several layers of ligaments, rendering extensive movements of the hyoid bones in the anteroposterior direction unlikely. Together with the manipulation of the 3D virtual model of the skull, these observations suggest that the hyoid arch is less mobile than previously proposed, and that the movements proposed in previous models are unlikely. In the light of our new observations, we suggest that the mechanisms proposed for explaining the intracranial elevation are incomplete. Moreover, we suggest that the extensive movements of the hyoid arch elements, which were thought to accompany intracranial elevation, are unlikely. In the absence of intracranial elevation, we propose that the movements of the hyoid mainly take place in the transverse plane, allowing the lateral expansion of the orobranchial chamber. Anat Rec, 298:579–601, 2015. © 2014 Wiley Periodicals, Inc.